The Effect of H-USY Catalyst in Catalytic Cracking of Waste Cooking Oil to Produce Biofuel - Rosmawati Rosmawati; Susila Arita; Leily Nurul Komariah; Nazarudin Nazarudin; Oki Alfernando (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2019)
The crisis in petroleum is caused by the diminishing supply of petroleum resources from nature. This phenomenon encourages researchers to continue to look for processes and methods to produce energy from other resources. One of these ways is to produce energy that can be utilized from waste, including converting waste cooking oil into biofuel. This method not only could provide a source of renewable energy, but also help resolve the issue of household waste. The process used to produce biofuel from waste cooking oil is by catalytic cracking, where waste cooking oil after pretreatment is converted into biofuel in the flow reactor with H-USY catalyst. In this research, the reaction temperatures used are 400 °C, 450 °C, 500 °C and 550 °C and reaction times are 30, 45 and 60 minutes with the mass ratio of the amount of waste cooking oil to the amount of catalyst used is 40:1 (w/w). The highest yield of liquid biofuel product was obtained at 60.98%. The use of H-USY catalyst shows that the distribution of components contained in biofuel are 28.02% of diesel products (C17 -C20), 23.96% of gasoline (C6 –C12) and 7.78% of Heavy oil (C20 >) in catalytic cracking of waste cooking oil with a reaction time of 45 minutes at a temperature of 450 °C.